Caulerpin: Biosynthetic Significance and Cytotoxic Activity Against Artemia salina Leach - Dini, Iwan (Hayyan Journal, 2025)
Caulerpin (1) is one of the bisindole alkaloid compounds isolated from the many macroalga species of the Halimeda and Caulerpa genera. The biosynthetic significance of 1 is suggested by the biotransformation of indole-3-acetic acid to indole-3-carboxaldehyde via tryptophan from the shikimate pathway. This compound has many biological activities reported and this time, the 1 were evaluated for their cytotoxicity in the brine shrimp assay against A. salina Leach. in vitro and showed moderate activity with IC50 value 81.28 µg/mL.